2017
DOI: 10.1155/2017/4208405
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pesticide Poisoning in Children: Hospital Review in Selected Hospitals of Tanzania

Abstract: Background Acute pesticide poisoning (APP) is a serious problem worldwide. Because the burden of childhood APP is unknown in Tanzania, this study describes the distribution, circumstances, and patterns of APP involving children under 18 years in Tanzania. Methodology A 12-month prospective study was conducted in 10 Tanzanian healthcare facilities in 2006 using a data collection tool for surveillance. Results Of 53 childhood poisoning cases identified, 56.6% were female. The most common poisoning circumstances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
1
14
0
1
Order By: Relevance
“…Which is supported by the observation of Robert JR et al and Lu C et al 10,11 But Dayasiri KC et al, has found that pesticide poison is more common in below 5years age group. 8 Most of cases of poisoning were accidental only 7.4% cases were having suicidal intent, which is supported by the work of Elikana lekei et al 12 Incidence of poisoning was more in rainy season and most of the patient were from rural area then urban this finding corroborates with the finding of Dayasiri et al and Rao CSH et al 7,8 In present study most, common pesticide consumed was chlorpyrifos, (29.36%) followed by monochrotofos.…”
Section: Discussionsupporting
confidence: 88%
“…Which is supported by the observation of Robert JR et al and Lu C et al 10,11 But Dayasiri KC et al, has found that pesticide poison is more common in below 5years age group. 8 Most of cases of poisoning were accidental only 7.4% cases were having suicidal intent, which is supported by the work of Elikana lekei et al 12 Incidence of poisoning was more in rainy season and most of the patient were from rural area then urban this finding corroborates with the finding of Dayasiri et al and Rao CSH et al 7,8 In present study most, common pesticide consumed was chlorpyrifos, (29.36%) followed by monochrotofos.…”
Section: Discussionsupporting
confidence: 88%
“…Children in this age range are the most vulnerable group to be exposed to household chemical poisoning (Awang et al, 2003;Lam, 2003;Gutierrez et al, 2011;Tangiisuran et al, 2018). They have a high prevalence of acute poisoning as they are likely to taste or swallow harmful substances (Haghighat & Moatamedi, 2012;Adnan et al, 2013) due to their behaviour; curious, exploratory in nature, and prone to putting things in their mouths (typical of early childhood development) (Lekei et al, 2017;Peshin & Gupta, 2018). Therefore, strict supervision by adults is mandatory, and the reflection of attitude and perception (belief) of parents may affect preventive action (Rosenberg et al, 2011).…”
Section: Attitudementioning
confidence: 99%
“…Ideally, most people are more agreeable to practise the right procedures that have scientific or evidence-based information (Brownson et al, 2009). In developing proper practices that may overcome poisoning cases, household chemical products management needs to be implemented appropriately (Lekei et al, 2017).…”
Section: Practicesmentioning
confidence: 99%
“…Medications and household cleaning substances are the most frequent contributors of childhood poisoning in developed countries [8] . On the other hand, pesticides are a significant contributor for childhood poisoning in developing countries where agricultural activities are common [24,25] . The poison agent in the current study was taken through the digestive system in 60% of the incidents.…”
Section: ~ 51 ~mentioning
confidence: 99%